Development and Characterization of 3D Printable Thermite Component Materials. Issue 12 (26th October 2018) - Durban, Matthew M.; Golobic, Alexandra M.; Bukovsky, Eric V.; Gash, Alexander E.; Sullivan, Kyle T.
Abstract: Additive manufacturing (AM) has recently shown great promise as a means to tailor a wide range of material properties, both quasi‐static and dynamic. An example of controlling the dynamic behavior is to tailor the chemical energy release rate in composite energetic materials such as thermites – which are a subset of pyrotechnics that use a metal fuel and a metal oxide as an oxidizer. Since these materials are most hazardous once finely mixed, the approach taken here is to formulate the fuel and oxidizer separately such that they can be mixed on‐the‐fly. Herein, the development, formulation, and characterization of two respective aqueous 3D printable inks consisting of Al and CuO are discussed. The rheological properties and ability of the material to span gaps are characterized. To demonstrate that the materials could be mixed and sustain a reaction, the inks are fed into a static mixing nozzle and extruded into a high‐aspect ratio test strip. Upon drying, the material can be ignited and sustain a propagation through the part. These results present a facile, and safe, way to AM thermite which can be used for more detailed follow on studies looking at the role of architecture on the reactivity. Abstract : The formulation and characterization of particle‐based aluminum and copper oxide constituent inks for additive manufacturing of thermites is investigated. The printability of the materials are evaluated, and the materials are mixed on the fly through a static nozzle to demonstrate a safe way of printing that, upon printing, yields a reactive composite.